School violence and levels of learning achievement in a public educational institution in Puerto Maldonado - Estrada Araoz, Edwin Gustavo (2020)
The objective was to establish the relationship between school violence and the levels of learning achievement of students in the fifth cycle of a public educational institution in Puerto Maldonado. The research approach was quantitative, the design non-experimental and the relational level. The data collection instruments were the AVE Test and the Consolidated Assessment Certificate. The results indicate that there is an inverse and significant relationship between school violence and levels of learning achievement (rs = -0.297; p = 0.021 <0.05). It was concluded that high levels of school violence are related to low levels of learning achievement.